The wilderness from chaberlain farm - Bennett Dean B. (Island Press, 2001)
Deep in the wildlands of northern Maine is a remote piece of land with a small point sheltering a shallow cove along the shore of an expansive lake. Used as a campsite by indigenous peoples for thousands of years, the land was cleared in the mid-1800s, developed into a lumber depot and named Chamberlain Farm. Following a period of neglect after a century of use by lumbermen, the area was turned into a rustic enclave for hunting and fishing enthusiasts. In recent years as civilization encroached, it became the focus of protection efforts by wilderness lovers who sought to ensure preservation and keep in it some semblance of its former wildness.